1998
DOI: 10.1080/10587259808047112
|View full text |Cite
|
Sign up to set email alerts
|

Waveguiding in a Nematic Hybrid Slab

Abstract: We develop an analytical approach to study the propagation of optical fields through a nematic slab model with hybrid boundary conditions studied numerically by Lin et al. [I]. For a low intensity beam we first derive the eikonal equation and from it we then calculate the ray trajectories in the limit of geometrical optics. We show that there may exist caustics within the slab. Then we consider the WKB limit and calculate the field transverse magnetic modes, their number and their cutoff frequencies. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The usual method to solve Maxwell's equations has been carried out in detail for a hybrid cell similar to the one considered here [37], and it is found that there is a regime for the incidence angle where the ray trajectory presents a caustic, that is, a geometrical place where the beam bends and remains inside the cell until it returns back towards the incidence substrate (see Figure 1). This trajectory is given by [37]…”
Section: Ray Propagationmentioning
confidence: 99%
“…The usual method to solve Maxwell's equations has been carried out in detail for a hybrid cell similar to the one considered here [37], and it is found that there is a regime for the incidence angle where the ray trajectory presents a caustic, that is, a geometrical place where the beam bends and remains inside the cell until it returns back towards the incidence substrate (see Figure 1). This trajectory is given by [37]…”
Section: Ray Propagationmentioning
confidence: 99%